Experts' Perceptions on China's Capacity to Manage Emerging and Re‐emerging Zoonotic Diseases in an Era of Climate Change. (23rd December 2016) - Hansen, A.; Xiang, J.; Liu, Q.; Tong, M. X.; Sun, Y.; Liu, X.; Chen, K.; Cameron, S.; Hanson‐Easey, S.; Han, G.‐S.; Weinstein, P.; Williams, C.; et al.
Summary: Zoonotic diseases transmitted by arthropods and rodents are a major public health concern in China. However, interventions in recent decades have helped lower the incidence of several diseases despite the country's large, frequently mobile population and socio‐economic challenges. Increasing globalization, rapid urbanization and a warming climate now add to the complexity of disease control and prevention and could challenge China's capacity to respond to threats of emerging and re‐emerging zoonoses. To investigate this notion, face‐to‐face interviews were conducted with 30 infectious disease experts in four cities in China. The case study diseases under discussion were malaria, dengue fever and haemorrhagic fever with renal syndrome, all of which may be influenced by changing meteorological conditions. Data were analysed using standard qualitative techniques. The study participants viewed the current disease prevention and control system favourably and were optimistic about China's capacity to manage climate‐sensitive diseases in the future. Several recommendations emerged from the data including the need to improve health literacy in the population regarding the transmission of infectious diseases and raising awareness of the health impacts of climate change amongst policymakers and health professionals. Participants thought that research capacity could be strengthened and human resources issues for front‐line staff should be addressed. It was considered important that authorities are well prepared in advance for outbreaks such as dengue fever in populous subtropical areas, and a prompt and coordinated response is required when outbreaks occur. Furthermore, health professionals need to remain skilled in the identification of diseases for which incidence is declining, so that re‐emerging or emerging trends can be rapidly identified. Recommendations such as these may be useful in formulating adaptation plans and capacity building for the future control and prevention of climate‐sensitive zoonotic diseases in China and neighbouring countries.